ANALYSIS OF ICONS, INDEXES, AND SYMBOLS IN YOUTUBE ADVERTISEMENT OF WARDAH PERFECT BRIGHT CREAMY FOAM FACIAL WASH - Sakinah, R. Myrna Nur; Alfiqri, Jimy; Hanifah, Lala Nur (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2020)
This study aims to determine the types of icons, indexes, and symbols contained in advertisements on YouTube about one beauty product named Wardah Perfect Bright Creamy Foam Face Wash. This ad aims to explain to the Indonesian people especially teenagers that to be beautiful it must look clean, healthy and shining. By caring for themselves and using certain products in order to highlight the characteristics of each without having to be someone else. The theory used in this research is the sign system theory with the Semiotics approach proposed by Charles Sanders Pierce. Where this theory can divide the sign system into three part namely icons, indexes, and symbols. The method used is a qualitative descriptive method that is applied to determine the contents of the overall meaning of Wardah Perfect Bright Creamy Foam Face Wash beauty products. As a research using descriptive research, this study only describes the writer's purpose in analyzing this advertisement, not looking for relationships, not testing hypotheses or making predictions. The data in this study are using qualitative data. In conducting this research, the writer collects, sorts, and groups the available data. Then the data are analyzed using the theory of semiotics, and finally the writer presents the results. Meanwhile, the writer found 3 data of the icon sign system, 3 data of the index sign system and 2 data of the symbol sign system. The overall data contained in Wardah Advertisement YouTube of Perfect Bright Creamy Foam Facial Wash is 8 data. Thus, it could be concluded that each advertisement had different sign and also different meaning. These differences had given different interpretations.